Creatine mitigates neurogenesis impairment caused by defective DcpS decapping - Jun Yang; Geeta Palsule; Xinfu Jiao; Jaime S. Messenger; Ronald P. Hart; Megerditch Kiledjian (Scientific Reports)
Abstract Biallelic mutations in the DCPS gene disrupting the decapping activity of the scavenger decapping protein DcpS, leads to neurodevelopmental deficiencies and intellectual disability. However, the molecular basis for the neurogenesis defects in these individuals remains unknown. Here we show that cells derived from individuals with a DCPS mutation harbor a creatine deficiency and a corresponding elevation of the creatine precursor, guanidinoacetate (GAA). The altered metabolite levels are a consequence of a reduction in both the mRNA and protein levels for the enzyme that converts GAA into creatine, guanidinoacetate methyltransferase. Importantly, the compromised neurogenesis and neurite outgrowth phenotypes observed during the differentiation of DcpS mutant patient derived induced pluripotent stem cells into neurons was reversed upon supplementation of creatine monohydrate. These findings suggest creatine deficiency as an underlying factor for the neurogenetic defect detected in DcpS mutant cells and a potential driver of the neurological deficiencies in affected individuals.